Could lengthening minocycline therapy better treat early syphilis?. Issue 52 (December 2016) - Shao, Li-Li; Guo, Rui; Shi, Wei-Jie; Liu, Yuan-Jun; Feng, Bin; Han, Long; Liu, Quan-Zhong
Abstract : Abstract: Syphilis is a sexually transmitted disease caused by Treponema pallidum . Minocycline, a representative tetracycline derivative, has the greatest antimicrobial activity among all tetracyclines. There are few reports about treating syphilis with minocycline because there is a lack of efficacy data from controlled trials. We compared the rates of serological cure in patients with early syphilis who were treated with minocycline or benzathine penicillin G (BPG). During the study period, a total of 40 syphilis patients received the BPG treatment, which was a single intramuscular dose of 2.4 million units of BPG, and 156 patients were treated with minocycline; 77 patients were placed in the 2-week, standard minocycline therapy group and received 100 mg of minocycline orally, twice daily for 14 days, and 79 patients were placed in the 4-week, lengthened minocycline therapy group and received 100 mg of minocycline orally, twice daily for 28 days. The outcome of interest was the rate of serological cure in these patients. At the end of the 2-year follow-up, the serological cure rate of the 4-week, lengthened minocycline therapy group (87.34%) was higher than that of both the 2-week, standard minocycline therapy group (72.73%) and the BPG treatment group (77.50%). In addition, the curative effect of the 4-week, lengthened minocycline therapy was significantly greater than that of the 2-week, standard minocycline therapy in patients who were aged >40 years; exhibited an initial rapid plasma reagin titer ≥1: 32; or exhibited secondary syphilis ( P = 0.000, 0.008, 0.000; <0.05). Minocycline appears to be an effective agent for treating early syphilis, especially when applied as a 4-week, lengthened therapy.